A review of the low-energy K−-nucleus/nuclei interactions with light nuclei AMADEUS investigations - Skurzok, Magdalena; Cargnelli, Michael; del Grande, Raffaele; Fabbietti, Laura; Guaraldo, Carlo; Marton, Johann; Moskal, Paweł; Piscicchia, Kristian; Scordo, Alessandro; Silarski, Michał; Sirghi, Diana Laura; Vazquez Doce, Oton; et al. (Frontiers in Physics, 2023)
The AMADEUS Collaboration conducts research aimed to experimentally investigate the low-energy K − hadronic interactions with light nuclei like hydrogen, helium, and carbon, in order to provide new constraints to the antikaon-nucleon strong interaction studies in the non-perturbative quantum chromodynamics regime. K − nuclear absorption, both at-rest and in-flight, are explored using the unique low-momentum and monochromatic kaon beam from the DAΦNE collider interacting with the KLOE detector components, a detector characterized by high acceptance and excellent position and momentum resolutions. This paper presents an overview of the AMADEUS results.